(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In this article as a social phenomenon problems of education and pedagogics in philosophical system of Al-Farabi are versatily considered. This phenomenon is closely connected with soul of the person and also confirms that each person since early years is going to become the member of society, to reach the level of perfection, and as a result to achieve the set goal. According to Al-Farabi, all activity directed on education is an of the person of values, knowledge and practical opportunities in society, in some period of time. If a main goal of education is achievement of perfection by the personality, the human life purpose in the world – to achieve the highest level of happiness – absolute good. Al-Farabi unites all levels of knowledge and practice in the purpose of receiving knowledge: any received theoretical knowledge has to be put into practice. Key words: Education, theory, practice, political leader, moral, personality, pedagogical, intellectual knowledge, didactics.